Development of a Detection System for ESR1 Mutations in Circulating Tumour DNA Using PNA-LNA-Mediated PCR Clamping - Yuki Kojima; Emi Noguchi; Tomomi Yoshino; Shigehiro Yagishita; Shu Yazaki; Hitomi S. Okuma; Tadaaki Nishikawa; Maki Tanioka; Kazuki Sudo; Tatsunori Shimoi; Ayaka Kazama; Hiroshi Terasaki; et al. (Diagnostics, 2023)
Although circulating tumour DNA (ctDNA)-based next-generation sequencing (NGS) is a less invasive method for assessing ESR1 mutations that are essential mechanisms of endocrine therapy resistance in patients with oestrogen receptor-positive breast cancer, adequate amounts of DNA are required to assess polyclonal ESR1 mutations. By combining a peptide nucleic acid and locked nucleic acid polymerase chain reaction (PNA-LNA PCR) clamping assay, we have developed a novel detection system to screen for polyclonal ESR1 mutations in ctDNA. A validation assay was prospectively performed on clinical samples and compared with the NGS results. The PNA-LNA PCR clamp assay was validated using six and four blood samples in which ESR1 mutations were detected by NGS and no mutations were detected, respectively. The PNA-LNA assay results were comparable with those of NGS. We prospectively assessed the concordance between the PNA-LNA PCR clamp method and NGS. Using the PNA-LNA PCR clamp method, ESR1 mutations were detected in 5 out of 18 samples, including those in which mutations were not detected by NGS due to small amounts of ctDNA. The PNA-LNA PCR clamping method is a highly sensitive and minimally invasive assay for polyclonal ESR1 mutation detection in the ctDNA of patients with breast cancer.